Family size and marital age - Helena Siregar; Azwin Lubis; M. Arif Nasution; Indra Kesuma Nasution; Thamrin Tanjung (Paediatrica Indonesiana, 1985)
A cross sectional study about the relationships between family size and marital age and the impact of educatimt, occupation and family planning programme was conducted in the region of South Tapanuli North Sumatera. The study was performed on 246 married couples by simple random sampling of households in the villages Pakantea, Tamiang, Muarasoro and Sumuran, during the period of September 25 up to October 3, 1982. The eariiest age of marriage for women was 14 years, ancl the latest 20 years. Most of the women (68%) married at 15-20 year. The main education of responders were primary school (67%). The occupational status was mostly (90%) farmer. The mean family size under 20 years old was 6.3 and over 20 years, 5.3. Fertility rate under 20 years was still high. Family Planning was not yet widely accepted in this area.